English Education Master Students' Perceptions on Metacognitive Strategy in Academic Reading - Wijaya, Kristian (LPPM Universitas Advent Indonesia, 2022)
Abstract Metacognitive strategy can bring about varied fruitful influential impacts toward academic reading enterprises endured by graduate university EFL learners. In this present small-scale qualitative study, the researcher aimed to profoundly investigate English Education Master Students’ perceptions on metacognitive strategy in academic reading. To achieve this research objectivity, this study employed a qualitative content analysis method to obtain more specific portrayals out of the gathered data. 10 online Likert-scale questionnaire items were distributed to 18 English Education Master Students, batch 2019, Sanata Dharma University, Yogyakarta. After obtaining the intended data from this first research instrument, the researcher also planned to make use of 5 open-ended written narrative inquiry questions to be responded to by 3 randomly selected interviewees derived from similar research samplings. Two major-specific themes were revealed namely: (1) Metacognitive strategy has successfully promoted more positive academic reading behaviors and (2) Metacognitive strategy allowed graduate university EFL learners to achieve more fruitful academic reading outcomes. The main conclusion of these aforementioned findings is the internalization of metacognitive strategy at the beginning of academic reading dynamics is indispensably crucial in which graduate university EFL learners can potentially transform into more mature, strategic, critical, and proficient L2 academic readers. Keywords: Metacognitive strategy, academic reading, students’ perceptions